THE CRAZE FOR STUDENTS’ NUMBERS IN KENYA’S PUBLIC AND PRIVATE UNIVERSITIES AND THE OPTIMAL OPERATION OF MASINDE MULIRO UNIVERSITY OF SCIENCE AND TECHNOLOGY: TOWARDS A COST RECOVERY STRATEGY - Odebero, Stephen O. (Machakos University, 2019)
From 2003 when the university came into being as a constituent college of Moi University up to 2013, Masinde Muliro University of Science and Technology (MMUST) had experienced unprecedented growth. Student population had grown tremendously. As of 2012/2013 academic year, student enrolment stood at 10,100 majority of who were enrolled in the Privately Sponsored programme (PSSP). The University had also witnessed growth in new programmes, departments, schools and faculties. Quite a reasonable number of infrastructural facilities had also been developed such as the library, science complex building and hostels (CHE,2011). The university had also expanded its wings in study centers and campuses. These included, Bungoma Campus, Sangalo campus, Webuye, Kaimosi, Kobujoi, Ebunangwe, Nambale, Budalangi, Busia, and Nairobi campuses among others. Despite these expansions, the University had faced myriad challenges.